FACTORS INFLUENCING TAXPAYER COMPLIANCE DURING THE COVID-19 PANDEMIC AT PT ADAM DANI LESTARI - Lansky, Jolin (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine and analyze the factors that influence taxpayer compliance at PT Adam Dani Lestari. The research method used is quantitative data, namely data obtained in the form of numbers or numbers. Source of data in this research is primary data that are obtained by distributing questionaries to 30 individual taxpayers who work at PT Adam Dani Lestari. The population in this study are 282 employees. The sample in this study used a purposive sampling technique with the criteria of employees having a Taxpayer Identification Number of as many as 30 people. Data analysis using multiple regression analysis method. The results of the analysis give the equation of Taxpayer Compliance = 8.366 + 0.315 Tax Incentives + 1.218 Tax Sanctions + e. The results of this study indicate that Tax Incentives on Taxpayer Compliance, Tax Incentives have no effect and are not significant on Taxpayer Compliance at Individual Taxpayers at PT Adam Dani Lestari based on a partial hypothesis test, namely with tcount < ttable with the sum of 0.095 < 2, 04841 and a significant value > 0.05, with the sum of 0.329 > 0.05. The results of this study indicate that Tax Incentives and Tax Sanctions on Taxpayer Compliance, Tax Sanctions have an effect and are significant on Taxpayer Compliance with Individual Taxpayers at PT Adam Dani Lestari based on simultaneous hypothesis testing, namely with a value of fcount > ftable, namely with the sum of 8.212 > 3.364 and a significant value < 0.005 with the sum of 0.002 > 0.005. The results of this study are supported by the value of R Square (R2) 0.378 or 37.8%, which means that taxpayer compliance can be explained by the variables of tax sanctions and tax incentives. While the remaining 62.2% of the Taxpayer Compliance variable can be explained by other variables not examined in this study, such as Taxpayer Awareness, Tax Audit, Tax Revenue, and Tax Knowledge.